2019
DOI: 10.1590/rbz4820170055
|View full text |Cite
|
Sign up to set email alerts
|

Optimal feeding frequency for Heros severus (Heckel, 1840), an Amazon ornamental fish

Abstract: The influence of feeding frequency on growth performance, batch uniformity, and survival rate of severum (Heros severus) larvae and juveniles was investigated in two experiments. In the first, 200 five-day-old severum larvae with 3.20±0.31 mg and 6.20±0.39 mm were randomly distributed into 20 aquaria (1 L) and fed 500 Artemia nauplii larvae −1 day −1 for 15 days. In the second, 120 severum juveniles, 178.19±33.59 mg and 1.82±0.09 cm, were randomly distributed into 15 aquaria (300 L) and hand-fed a commercial d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 23 publications
1
4
1
Order By: Relevance
“…Paixão et al (2019) reported that the uniformity of length and weight of severum ( H. severus ) did not show significant differences at the end of 30 days regardless of feeding frequency, however the results of present study, uniformity of the weight of banded cichlid was decreased after 90 days, which is caused by the lower availability of food and competition within of trial unit. According to Wang et al (1998), smaller feeding frequency can favor a smaller number of fish into rearing system, making it less uniform.…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…Paixão et al (2019) reported that the uniformity of length and weight of severum ( H. severus ) did not show significant differences at the end of 30 days regardless of feeding frequency, however the results of present study, uniformity of the weight of banded cichlid was decreased after 90 days, which is caused by the lower availability of food and competition within of trial unit. According to Wang et al (1998), smaller feeding frequency can favor a smaller number of fish into rearing system, making it less uniform.…”
Section: Discussioncontrasting
confidence: 80%
“…Growth performance of H. severus submitted to feeding frequency two and four times a day have no statistical difference ( p > 0.05) as observed by Paixão et al (2019), juveniles of Jundiá Rhamdia quelen reared in excavated tank (Canton Weingartner et al, 2007), production of robalo‐peva Centropomus parallellus in fresh water (Corrêa Gervazio et al, 2010) and rearing of tilapia Oreochromis niloticus (Santos et al, 2014).…”
Section: Discussionmentioning
confidence: 78%
“…However, the electrical conductivity in the treatments without addition of salt was 0.34 ± 0.11 mS cm -1 , whereas in those that had the salinized water the values were of 4.98 ± 0.28 mS cm -1 and 9.81 ± 0.17 mS cm -1 for 3 and 6 g L -1 of salt, respectively. Nevertheless, the parameters of water quality remained within the appropriate condition for H. severus larviculture (Eiras et al, 2019;Paixão et al, 2019).…”
Section: Parameters Of Water Qualitymentioning
confidence: 99%
“…In that sense, Heros severus stand out as a specie with high potential for the ornamental market due to its calm behavior, quick adaptation to new environments, easy reproduction, and beautiful coloration (Alishahi et al 2014, Veras et al 2016. In its natural habitat, H. severus is associated with areas with high vegetation and feeds on small invertebrates and vegetal material (Soares et al 2019).…”
Section: Introductionmentioning
confidence: 99%